WD repeat domain 62 (WDR62) promotes resistance of colorectal cancer to oxaliplatin through modulating mitogen-activated protein kinase (MAPK) signaling. Issue 6 (1st June 2022) - Cai, Juanjuan; Su, Lingling; Luo, Weiwei
ABSTRACT: WD repeat domain 62 (WDR62) is involved in embryonic brain growth through regulation of glial and neural cell populations. WDR62 is also implicated in the carcinogenesis of various cancers. The role of WDR62 in progression and chemoresistance of colorectal cancer (CRC) was investigated. Firstly, oxaliplatin-resistant CRC cells (HCT116/R and HT29/R) were sequentially exposed to an increasing concentration of oxaliplatin. The results showed that WDR62 was elevated in CRC tissues, and oxaliplatin resistance conferred up-regulation of WDR62 in CRC cells. Knockdown of WDR62 reduced cell proliferation and promoted the apoptosis of oxaliplatin-resistant CRC cells. Moreover, silencing of WDR62 increased fluorescence intensity of γH2AX, and decreased protein expression of p-DNA-PK and Rad51 in the oxaliplatin-resistant CRC cells. The protein expression of p-ERK, p-JNK, and p-p38 in oxaliplatin-resistant CRC cells were down-regulated by knockdown of WDR62. In conclusion, silencing of WDR62 suppressed oxaliplatin resistance and DNA damage repair of CRC cells through inactivation of MAPK signaling. graphica abstract: uf0001